Analysis of Customer Satisfaction Levels in Purchasing Plastic Flower Crafts in Pematangsiantar using the Rought Set method - Putri, Adelia; Lubis, Aditya Rifki; Anarki, Lintang Lantang Jagad (JOMLAI: Journal of Machine Learning and Artificial Intelligence, 2023)
Customer satisfaction is a key indicator in assessing the quality of service and a product, reflecting the extent to which customer expectations are met after purchasing or interacting with a product.This study applies the Rought Set algorithm to analyze customer satisfaction based on condition attributes such as Flower Type, Color, Size, Price and Quality, with the decision attribute being the Satisfaction Level.The research data was conducted by means of a field survey by distributing questionnaires to a sample of customers in Pematangsiantar.The data classification process was carried out with the Rosetta application. The research resulted in 13 reductions with 116 rules connecting the condition attributes and the level of satisfaction.The results show that the Rought Set algorithm can perform the classification quite well.The conclusion of this study is to use the Rought Set algorithm in classifying the level of satisfaction in purchasing plastic flower crafts for customers in Pematangsiantar.This research is important with the aim of developing the level of customer satisfaction in purchasing plastic flower crafts in Pematangsiantar such as product quality, and the Rought Set algorithm is useful in analyzing the level of customer satisfaction.